An integrative taxonomic study of Susanlimocotyle narina n. gen. n. sp. (Monogenoidea, Dactylogyridae) from the nasal cavities of a marine catfish (Siluriformes, Ariidae) from the Atlantic Amazon Coast of Brazil and new molecular data of Chauhanellus spp. (April 2021) - Soares, Geusivam B.; Domingues, Marcus V.; Adriano, Edson A.
Abstract: Based on a taxonomic approach, combining morphological characters with DNA sequences ( i.e., 18S rDNA, ITS1, 5.8S rDNA and ITS2), Susanlimocotyle n. gen. is proposed to accommodates Susanlimocotyle narina n. sp. from the nostrils of the ariid Sciades herzbergii (Bloch) from the coast of the state of Pará, Brazil. Susanlimocotyle n. gen. is characterized by species possessing: an intestinal ceca confluent posteriorly; a male copulatory organ, comprising a variable tube, articulated with the accessory piece; a sclerotized vagina, vaginal aperture dextro-ventral; an onchium; a robust ventral bar; two dorsal bars; a ventral anchor with elongated shaft and a dorsal anchor with deep root expanding into wings. In addition, new molecular data of Chauhanellus spp. are also provided and used for the evaluation of the phylogenetic relationships among monogenoids parasitizing siluriforms. Susanlimocotyle n. gen. exhibited a higher genetic divergence level for 18S rDNA (4.6 to 7.2% [83–130 bp]) with respect to Chauhanellus spp. despite sharing S. herzbergii as a host, than Hamatopeduncularia spp., (4.1 to 5.8% [75–110 bp]) from Oriental ariids. For the 18S rDNA, 5.8S rDNA, ITS1 and ITS2 regions, C. boegeri and C. susamlimae were observed to have the smallest interspecific distances, and C. velum was revealed to be the most genetically distant species to Chauhanellus . The proposal for Susanlimocotyle n. gen. is also supported by phylogenetic analysis based on the 18S rDNA gene, which supports the close relationship between the new genus and Hamatopeduncularia and Chauhanellus from ariids from the South America and Oriental regions. Moreover, the patterns towards the shared diversification between monogenoids and their ariid hosts were addressed. Graphical abstract: Unlabelled Image Highlights: Susanlimocotyle narina n. gen., n. sp. is described by using an integrative taxonomic approach. Susanlimocotyle n. gen. can be distinguished from monogenoids from ariids based on morphologic and molecular data. Susanlimocotyle narina n. gen., n. sp. is closely related to dactylogyrids from Oriental ariids. New molecular data of Chauhanellus spp. are also provided. Phylogeny of monogenoids infecting ariids reveals a patterns towards diversification shared of these parasites.